Karakteristik Pakaian Muslimah dalam Perspektif Al-Qur’an Surah Al-A’raf Ayat 26 - Adrianto; Haslinda; Sitorus, Khalid (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2024)
The clothing worn by many Muslim women today often does not align with the guidelines outlined in the Qur'an and is more frequently perceived as a fashion statement on social media. This study aims to analyze the views of prominent mufassirs on Muslim women's clothing based on Qur'anic exegesis, specifically regarding the obligation to cover the aurat. The method used is qualitative analysis, comparing the interpretations of two leading mufassirs, Ibn Kathir and M. Quraish Shihab, regarding the verses that address clothing and aurat. The findings show that, according to both mufassirs, the characteristics of Muslim women's clothing include non-transparent, non-tight, and non-attention-grabbing attire. Although there are differing views on the boundaries of a woman's aurat, both mufassirs agree that covering the aurat is an obligation that must be fulfilled with clothing in accordance with Islamic law, and that the best attire is taqwa clothing. This study concludes that Muslim women should maintain their honor and be cautious in their social interactions to avoid being influenced by the changing times. The world is a temporary place, while the afterlife is the eternal home. The contribution of this study is to provide an understanding of the mufassirs' perspectives on Muslim women's clothing and its relevance to the lives of Muslims in the modern era.